Genetic polymorphism of FASN gene and its relationship to some body dimensions, growth, and fertility traits in Awassi sheep - Hassan, Marwa; Hameed, Abdullah Hameed Salim (University of Thi-Qar Journal of agricultural research, 2025)
Abstract: The study was conducted at the Sheep and Goat Research Station in Al-Shatra District, north of Thi-Qar, affiliated with the Thi-Qar Agriculture Directorate, and included 39 ewes of the Awassi sheep breed. The study aimed to analyze the genotyps of the FASN gene using the sequencing technique and to determine its relationship with growth traits, body dimensions, and fertility rate. DNA sequencing results in exons (39-38-37, 617 base pairs long) showed no mutations, while sequencing of exons (20-19-18) of 997 base pairs revealed a C>G mutation at position 562 within exon 20, resulting in an amino acid change from leucine to Valine. It is a missense mutation. Three genotypes have been identified (CC, CG, GG). The wild type (CC) was the most common (53.1%), with an allelic frequency of 0.69 for the C allele and 0.31 for the G allele. The results showed a significant effect of FASN gene genotypes on the rear height trait; CG ewes outperformed GG and CC ewes. A significant effect was also recorded on the birth weight of the fetus, with the GG combination being superior, without any significant differences being recorded in the fertility rate between the three combinations. The study concludes the importance of the FASN gene as a genetic indicator for improving productive performance in Awassi sheep by selecting genetic combinations associated with the best productive traits.